Polymerization of Ethylene Glycol Dimethacrylate (EGDM), Using An Algerian Clay as Eco-catalyst (Maghnite-H+ and Maghnite-Na+) - Sara Haoue; Hodhaifa Derdar; Mohammed Belbachir; Amine Harrane (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
In this paper we have explored a novel and green method to synthesis and polymerize ethylene glycol dimethacrylate (EGDM). This technique consists on using Maghnite (Algerian clay) as a green catalyst to replace toxic catalysts. The Algerian clay has been modified using two ion exchange process to obtain Maghnite-H+ (proton exchanged process) and Maghnite-Na+ (sodium exchanged process). Synthesis experiments of EGDM and Poly (EGDM) are performed in bulk respecting the principles of green chemistry. The structure of the obtained monomer and the obtained polymer was confirmed by FT-IR, 1H-NMR and 13C-NMR, where the methacrylate end groups are clearly visible. The presence of unsaturated end group in the structure of monomer was confirmed by UV-Visible analysis. Thermogravimetric analysis (TGA) was used to study the thermal stability of these obtained products. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).